Evaluation of kinetic and static methods of monitoring with GNSS systems after calibration in the Mobile Topographer pro application on the smartphone - غطروف, ماهر; فايز ديب; ندى محفوض (Latakia University Journal -Engineering Sciences Series, 2024)
The development of low-cost Global Navigation Satellite System (GNSS) chips has inspired the development of advanced positioning, navigation, and timing devices. Due to their low cost, GNSS chips are now ubiquitous, such as smartphones, tablets, and wearable smart watches, with consumer GNSS receivers positioning accuracy of several meters under conditions an ideal observation, its accuracy is reduced to tens of meters under more complex observational conditions. In this research, the accuracy of each of the following was evaluated: - Syrian stereographic horizontal coordinates before calibrating the application. - Syrian horizontal stereographic coordinates after calibrating the application on one of the known coordinate points. The results are presented in tables and graphs. The mean square error was around σ∆x= 0.659m and σ∆y= 0.518m after calibration and σ∆x= 2.945m and σ∆y= 2.379m before calibration. Through the results, the application can be used after calibration in geographic information systems and in real estate business.